Masterplanning for change. Designing the resilient city. - Rómice, Ombretta; Porta, Sergio; Feliciotti, Alessandra (RIBA Publishing, 2020)
Cities are under increased pressure to be resilient and resistant to the effects of climate change and rapid urbanisation. However, this idea has still not been fully integrated into practice. This book presents a practical approach to masterplanning the city and its areas (existing and new) as urban environments for the 21st century, addressing the design of cities as complex adaptive systems.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Resilienz; Klimaanpassung; Stadtgestaltung; Stadtanalyse; Strategieansatz; Konzeptplanung; Transformation; Planungstheorie